Assessment of Genetic Relationship Among Landraces of Bangladeshi Ridge Gourd (Luffa acutangula Roxb.) Using RAPD Markers - Hoque, S.; Rabbani, M. G. (Journal of Scientific Research, 2009)
Information on genetic relatedness among ridge gourd (Luffa acutangula) genotypes from Bangladesh is currently not reported. Twenty eight accessions collected from different parts of Bangladesh were studied using random amplified polymorphic DNA (RAPD) technique. Four selected decamer primers, out of sixteen screened, could generate a total of 27 RAPD fragments of which 22 were polymorphic (81.5%). The bands ranged from 50 to 1500 bp in size. Genetic variation statistics for all loci estimated the average gene diversity (h) value as 0.278 and the Shannon’s Information Index (I) as 0.415. Dendrogram based on unweighted pair-group method with arithmetic averages (UPGMA) segregated the accessions into five clusters. Cluster III was the largest with 13 members followed by cluster II, V, I and IV with 6, 4, 3 and 2 members, respectively. Accession LA27 and LA29 were found very close to each other with the highest inter-variety similarity index (96.05%) and the lowest genetic distance (0.077); whereas accession LA40 and LA72 were more distant to each other with the lowest inter-variety similarity index (44.43%) and the highest genetic distance (0.73). A DNA extraction method has been standardized. The marker was found to be useful tool for assessing genetic variations in Luffa acutangula. Keywords: Genetic relationship; Germplasm; Ridge gourd; Luffa acutangula; RAPD. © 2009 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. DOI: 10.3329/jsr.v1i3.1968 J. Sci. Res. 1 (3), 615-623 (2009)